The Evolution of OES ся: a Corpus Investigation - Györfi, Beáta (SlavVaria, 2024)
The present study focuses on the Old East Slavic reflexive pronominal enclitic ся. The research of the syntactic behaviour and historical evolution of this element thus far has been hindered by the vast amount of data. The application of corpus linguistics and statistical analysis, however, offer fresh avenues for understanding the complexities of this pronoun.